Mitologi “Bencana adalah Azab” dalam Meme Media Sosial - Atropal Asparina; Karina Rahmi Siti Farhani (UIN Sunan Gunung Djati, 2020)
This article examines the responses to natural disasters that are demonstrated through memes which are then spread through social media. The response in the form of a meme not only contained condolences or positive prayers related to disaster victims. But more than that, which contains a kind of warnings which essentially states that natural disasters that occur are the result of human hands or the disaster is God's punishment for disobedience by humans. Theological justification was finally used in the meme by quoting verses from the Quran, hadith of the Prophet or qaul of sahabat and scholars. As a result, both ethically or psychologically, memes that had been addressed as a warning and other forms of concern for disaster victims, made victims of such disasters get a double burden, in the end. Through semiotic analysis, specifically the mythical theory of Roland Barthes, the meme will be critically analyzed. As a result, memes that contain the stigma that disaster is God's punishment, is a myth that is unconsciously constantly being reproduced to commemorate others. In fact, in addition to the disaster is God's punishment, both in the Quran, hadith, and the meaning of disaster from scholars indicate another possibility that is equally strong, namely as a challenge, which of course has a different ethical and psychological impact on the victims of the disaster.